α-lipoic acid: drug or dietary supplement? An overview on the pharmacokinetics, available for-mulations and clinical evidence in the diabetes complications - Brufani, Mario (Progress in Nutrition, 2014)
α-lipoico acid, also known as 1,2-dithiolane-3-pentanoic acid or thioctic acid, due to its chiral carbon atom, has got two enantiomers R and S whose R-enantiomer is more biologically active and it is the only one naturally occurring. α-lipoico acid is an essential endogenous cofactor of important enzymatic complexes required to produce energy. Its amphiphilic property greatly enhances its ability to distribute in all the organism, including the central nervous system. Due to its oxidized and reduced (ALA/DHLA) forms, α-lipoico acid is a powerful antioxidant able to inactivate free radicals and reactive oxygen species, as well as enhance the activity of other endogenous antioxidants (such as vitamin C, vitamin E and glutathione) by regenerating or increasing their cellular levels. ALA is also able to effectively chelate various heavy metals limiting their toxicity. Furthermore, as confirmed by various studies, ALA helps to reduce blood glucose levels allowing glucose uptake and enhancing insulin sensitivity in patients with type 2 diabetes. While the rate of absorption of ALA administered through oral formulations such as tablets is only 37% of the initial dose, ALA administration through liquid formulations greatly improves the pharmacokinetic parameters (Cmax, AUC, Tmax). ALA has been widely used in the treatment of diabetic neuropathy: a review of these clinical studies confirms that the beneficial effect of ALA on neuropathic symptoms is obtained with 600 mg iv/day for 3 weeks or orally for 5 weeks, improving both control of pain and trophism and function of the nerve fibers, with good tolerability. In particular, due to the numerous potentials of the molecule, the new oral liquid formulation is very interesting because it shows some basic requirements for improving the ALA pharmacokinetic profile and therapeutic efficacy.